Headache impact and socioeconomic status: findings from a study of the German Migraine and Headache Society (DMKG) - Britta Müller; Charly Gaul; Olaf Reis; Tim P. Jürgens; Peter Kropp; Ruth Ruscheweyh; Andreas Straube; Elmar Brähler; Stefanie Förderreuther; Jennifer Schroth; Thomas Dresler (The Journal of Headache and Pain, 2023)
Abstract Backgound Headache disorders are not only among the most prevalent, they are also among the most disabling disorders worldwide. This paper investigates the association between headache impact on daily life and the socioeconomic status (SES) of headache sufferers. Methods Data stem from a random general population sample in Germany. Respondents who reported having headache for at least a year and were aged ≥ 18 years were included in the study. A standardized questionnaire addressing headache and headache treatment was filled in during the face-to-face survey. The impact of headache on daily life was measured using the German version of the Headache Impact Test (HIT-6). Results Higher headache impact was found in low and medium SES compared to high SES. After adjustment for sociodemographics, headache-related factors (analgesic use, headache duration, headache frequency, migraine diagnosis), depressive symptoms, physical inactivity and obesity, an increased odds ratio of having higher headache impact in low SES compared to high SES was found: OR = 1.83, 95% CI [1.43, 2.23], p = .014. When the interactions "SES*obesity", "SES*depressive symptoms", and "SES*physical inactivity" were added, the results showed a significant interaction effect of “SES*obesity”. Obese persons with low SES were 3.64 times more likely to have higher headache impact than non-obese persons with low SES. No significant differences between obese and non-obese persons were found in the medium and high SES groups. Conclusions SES is an important factor that should not be neglected in headache awareness campaigns and headache treatment. Longitudinal studies are needed in the future to investigate whether lifestyle interventions, such as weight reduction, can help to reduce headache impact in people in lower SES.